Design and Development of A Web-Based Information System for Zakat Management And Monitoring At Lazisnu Pati - Windy Alayda; Endang Supriyati; Tri Listyorini (SAGA: Journal of Technology and Information System, 2025)
This research presents the design and development of a web-based Zakat Information System at LAZISNU Pati aimed at improving transparency, efficiency, and accountability in zakat management. Zakat, a core Islamic obligation, requires institutions to uphold Sharia principles including amanah (trust), adl (justice), and hisbah (accountability). Existing digital platforms mainly address administrative processes, offering limited donor access and real-time monitoring. Using a Research and Development (R&D) approach combined with the Waterfall model, the system was implemented with Python Flask, MySQL, HTML/CSS/JavaScript, Midtrans, and WhatsApp API integration. Data were collected through observation, interviews, and documentation. System evaluation employed Black Box Testing and User Acceptance Testing (UAT) with muzakki and admin participants. Findings indicate that the system effectively supports registration, payment, unique code generation, distribution management, and reporting, while users reported high satisfaction with usability and clarity. By incorporating traceable transactions, nisab-based validation, automated notifications, and dashboards, the platform operationalizes Sharia values and fosters ethical zakat governance. This scalable, web-based system provides a practical model for enhancing digital governance and public trust in Islamic social finance institutions in Indonesia.